Implementation of Online-Based Arabic Teaching Communication during the Covid 19 Pandemic in the Communication Science Study Program of Communication and Islamic Broadcasting Study Program at UIN Antasari Banjarmasin - Safiah, Shapiah (Jurnal Al-Maqoyis, 2022)
Corona Virus Disease or commonly known as Covid 19 is still a polemic in almost all countries in the world, its impact covers all aspects of life, including the education sector. Since the implementation of the PSBB (Large-Scale Social Restrictions) program in major cities in Indonesia, making educational facilities completely closed and only carried out through online media. This research focuses on the Implementation of Online-Based Teaching Communication during the Covid 19 Pandemic carried out by the Islamic Communication and Broadcasting study program at UIN Antasari Banjarmasin using descriptive qualitative methods that refer to the theory of Computer Mediated Communication. The results show that the implementation of online-based teaching communication is carried out as follows: 1. The use of an integrated online portal, 2. Minimizing constraints on the internet network, 3. Shortening the duration of classes in virtual spaces, 4. Opening means of communication through various online applications, 5. Innovation in online learning features.